2012
DOI: 10.1242/dev.082396
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel developmental mechanism in the generation of mesothelia

Abstract: SUMMARYMesothelium is the surface layer of all coelomic organs and is crucial for the generation of their vasculature. Still, our understanding of the genesis of this essential cell type is restricted to the heart where a localized exogenous population of cells, the proepicardium, migrates to and envelops the myocardium supplying mesothelial, vascular and stromal cell lineages. Currently it is not known whether this pattern of development is specific to the heart or applies broadly to other coelomic organs. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 43 publications
(54 reference statements)
2
36
0
Order By: Relevance
“…To our surprise, we instead determined that unlike the heart, the avian intestinal splanchnic mesoderm housed broadly distributed mesothelial progenitors that differentiated in situ rather than from an external migratory population. This provided the first experimental evidence of an alternative model of mesothelial formation (19). …”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…To our surprise, we instead determined that unlike the heart, the avian intestinal splanchnic mesoderm housed broadly distributed mesothelial progenitors that differentiated in situ rather than from an external migratory population. This provided the first experimental evidence of an alternative model of mesothelial formation (19). …”
Section: Introductionmentioning
confidence: 81%
“…However, it is unknown whether the mechanisms of cardiac mesotheliogenesis, in particular the requirement to recruit exogenous mesothelial cell progenitors to the developing organ, are applied broadly throughout vertebrate organogenesis. We recently reported the intestine employed an alternative mechanism of mesothelial formation – generation of mesothelium from a broadly-distributed intrinsic population of progenitors (19). Still, the question remains as to whether a major conserved mechanism in this process is observed.…”
Section: Discussionmentioning
confidence: 99%
“…The CE Generates the Mesenchyme of the DM and Subaortic Region by Epithelial-to-Mesenchymal Transition The appearance of mesenchymal cells during formation of the DM, together with observations of other groups (Gros and Tabin, 2014;Richard et al, 2013;Winters et al, 2012;Winters et al, 2014), suggested that epithelial-to-mesenchymal transition (EMT) of the CE may be important for formation of the DM and ventral mesenchyme. To explore this possibility, we performed fate mapping by electroporating a constitutive GFP-expressing plasmid into the CE on one side of the embryo ( Figure 1K).…”
Section: Formation Of the Dorsal Mesentery And Ventral Body Structuresmentioning
confidence: 98%
“…During development, mesothelium lining the heart, liver, lungs and gut differentiate into vascular smooth muscle cells, interstitial fibroblasts, hepatic stellate cells, endothelial cells and adipocytes323334353637. More recently, adult mesothelial cells have also been shown to undergo MMT and differentiate into vascular smooth muscle cells, adipocytes and osteoblasts43839 and are likely to play important roles in fibrogenesis40.…”
Section: Discussionmentioning
confidence: 99%